Ben Jonson, dramatist - Barton, Anne 1933-2013 (Cambridge University Press, 1984)
Since the Romantic period, Jonson has been an author more respected than read. Frequently compared with Shakespeare, he usually suffers unfairly from the comparison. In this book Anne Barton gives a reading of the plays which completely re-evaluates Jonson as a dramatist. Describing in detail his experimentation with different comic styles and his changing relationship to other Elizabethan and Jacobean poets, particularly Shakespeare, she brings us closer than ever before to Jonson as a man, and as a great artist in comedy. The book proceeds chronologically, play by play, examining such important topics as Jonson's treatment of women, trust among individuals, father and son relationships, and proper names. Anne Barton argues that, despite his espousal of classical principles of decorum and restraint, Jonson was always drawn temperamentally towards the irregular, romantic Elizabethan tradition